Unraveling the influence of α-mangostin on MDA-MB-231 cell line via WNT/β-catenin signaling pathway: in silico and in vitro approaches - Amalia, Riezki; Dewi, Citra; Fristiohady, Adryan; Fakih, Taufik Muhammad; Muchtaridi, Muchtaridi (Frontiers in Pharmacology, 2025)
The Wnt/β-catenin signaling pathway is critically involved in breast cancer progression, particularly in the triple-negative subtype (TNBC). Aberrant activation of this pathway promotes tumor proliferation, with β-catenin functioning as a central effector regulated by GSK-3β-mediated phosphorylation and degradation. Despite its therapeutic significance, no selective Wnt/β-catenin inhibitors have been clinically approved, underscoring the need for alternative strategies. Natural compounds such as α-mangostin have emerged as potential modulators of this pathway. This study investigates the potential of α-mangostin, a natural xanthone compound, to suppress Wnt/β-catenin signaling through complementary in silico approaches examining its interaction with proteins related to the Wnt signaling pathway, followed by in vitro validation using the MDA-MB-231 triple-negative breast cancer cell line (ER-/PR-/HER2-). In parallel, MCF-7 cells (ER+/PR+/HER2-) were used as a comparator to evaluate the differential inhibitory effects on breast cancer cells with distinct hormonal profiles. Molecular docking demonstrated favorable binding of α-mangostin to β-catenin and LRP6, with higher affinity toward LRP6. Molecular dynamics simulations confirmed the stability of these complexes, particularly the α-mangostin-LRP6 complex, which exhibited minimal RMSD and SASA fluctuations. Consistently, MM/PBSA calculations revealed the most favorable binding free energy for α-mangostin with LRP6 (−96.659 kJ/mol). In vitro WST-8 assays revealed that α-mangostin reduced cell viability in both cell lines, with a greater suppressive effect observed in combination with LiCl. Treatment with 10 µM α-mangostin, alone or with LiCl, significantly downregulated the Wnt transcriptional targets CCND1 (5.2-fold) and MYC (3.3-fold) in MDA-MB-231 cells, as determined by RT-qPCR, thereby indicating a potent suppressive effect on the Wnt pathway. Collectively, these findings indicate that α-mangostin exerts anticancer effects by targeting multiple components of the Wnt/β-catenin pathway, with LRP6 emerging as its primary target. Further investigations are warranted to elucidate its impact on β-catenin phosphorylation and to validate its efficacy in vivo.